Effects of pre-germinated brown rice treatment high-fat diet-induced metabolic syndrome in C57BL/6J mice. Issue 5 (4th May 2017) - Yen, Hsueh-Wei; Lin, Hui-Li; Hao, Chi-Long; Chen, Fu-Chih; Chen, Chun-Yun; Chen, Jia-Hao; Shen, Kuo-Ping
Abstract: To investigate using pre-germinated brown rice (PGBR) to treat metabolic syndrome, we fed one group of mice standard-regular-diet (SRD) for 20 weeks and another group of mice high-fat-diet (HFD) for 16 weeks. We subdivided them into HFD group and HFD + PGBR group whose dietary carbohydrate was replaced with PGBR for 4 weeks. The HFD group gained more weight, had higher blood pressure, heart rate, blood glucose and lipids, liver levels of TG, feces TG and bile acid, lower adipose levels of adipocytokine, lower skeletal muscle IR, IRS-1, IRS-2, PI3 K, Akt/PKB, GLUT-1, GLUT-4, GCK and PPAR-γ; higher liver SREBP-1, SCD-1, FAS, HMGCR, LDLR, CYP7α1 and PPAR-α, and higher adipose SREBP-1, SCD-1, FAS, and lower adipose PPAR-α and adiponectin. The HFD + PGBR group had clearly improved blood pressure, biochemical parameters and above proteins expressions. PGBR successful treatment of metabolic syndrome was achieved through improvements in glucose and lipid synthesis and metabolism. Graphical abstract: : PGBR treats HFD-induced metabolic syndrome through improving glucose and lipid synthesis and metabolism.